Correlation between Exposure to Bomechanical Stress and Whiplash Associated Disorders (WAD) - William HM Castro (Pain Research and Management)
One of the most discussed questions in WAD is: can an injury of the cervical spine occur in low velocity collisions? Before this question can be answered, the term 'low velocity' and the kind of collisions must first be defined. From the study of Meyer et al. (1994) it is known that the speed change due to collision, Dv, is a suitable parameter to express the biomechanical stress acting on a person in a car collision. This study also showed that from a biomechanical point of view, a bumper car collision is comparable to a normal car collision. In the case of a rear-end collision, Meyer et al. found that the biomechanical stress acting on persons exposed to bumper car collisions (Dv) at a fun fair in Germany can be as high as 15 km/h. In literature, one case could be found of an 8-year-old girl with 'whiplash' after being exposed to a bumper car collision at a fun fair (Kamieth 1990). In the Netherlands, a 13-year survey of persons who were admitted to emergency units of hospitals by the 'Consument en Veiligheid' foundation, showed 14 persons with WAD complaints after being exposed to bumper car collisions at a fun fair. In comparison to the enormous amounts of bumper car collisions, these figures are negligible. With regard to these data, one could argue that low velocity collisions can be defined as those where Dv is below 15 km/h. However, it should be noted that the kind of collision is important. From the work of Becke et al. (1999) and Becke and Castro (2000), we know that in side collisions with a Dv of just 3 km/h, head contact with the side window of the car is possible; it can be expected that in such cases the cervical spine will also be exposed to some biomechanical stress (notice however, that not every head contact is automatically equal to an injury of the cervical spine!). In conclusion, before using expressions like 'low velocity collisions', its definition with regard to Dv as well as the kind of collision, has to be discussed. With regard to the most common collisions that causes WAD, rear-end collisions, low velocity collisions can arguably be defined as collisions where Dv is below 15 km/h (this is for clarity, and does not mean that those collisions can not cause symptoms; this will be discussed later!).